2003
DOI: 10.1002/bin.127
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of dangerous behavior

Abstract: Individuals who display dangerous behavior towards others have historically been under-treated and under-researched. This paper discusses three published case studies wherein adult males were effectively treated for severe aggression towards others, the environment, and, in two cases, self-injury. All were diagnosed as having mental retardation and two also had a psychiatric diagnosis. All had experienced years of failed attempts to control their aggression through large pharmacological interventions and restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Yet as discussed previously (Foxx et al, 1989) using positive reinforcement alone at the beginning of treatment (see Foxx, 2005a and b) would not only be dangerous but also noncompetitive with the powerful negative reinforcement that is available. This is why the most honest, effective, and appropriate model was demonstrated in the present case in that Johnny's responsiveness to positive approaches greatly increased over time after his aggression was first brought to safe levels with appropriate reductive and positive procedures (Foxx, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…Yet as discussed previously (Foxx et al, 1989) using positive reinforcement alone at the beginning of treatment (see Foxx, 2005a and b) would not only be dangerous but also noncompetitive with the powerful negative reinforcement that is available. This is why the most honest, effective, and appropriate model was demonstrated in the present case in that Johnny's responsiveness to positive approaches greatly increased over time after his aggression was first brought to safe levels with appropriate reductive and positive procedures (Foxx, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…2005). Foxx (2003) has suggested aversive punitive treatment in certain cases with similar behaviours, especially of the premeditated type.…”
Section: Improving the Diagnostic And Treatment Process Of Aggressivementioning
confidence: 99%
“…It can be difficult to work with clients who selfinjure for multiple reasons. One of the main reasons, and predicaments, is that SIB can become worse before it ever improves (Foxx, 1982(Foxx, , 2003. SIB typically serves as a coping mechanism that is activated by an increase in emotional arousal (Favazza, 1987;van der Kolk, Perry, & Herman, 1991;Winchel & Stanley, 1991), and it assists the client in gaining a feeling of control or relieving tension (Gardner & Gardner, 1975).…”
Section: Reasons For Self-injurymentioning
confidence: 99%
“…Zila and Kiselica (2001) reported that limited information on SIBs in the literature frequently hinders proper treatment and can ultimately lead to a counselor's frustration, repulsion, or fear of the behavior. However, regardless of the treatment method, SIB can increase in frequency and severity when a client begins to work on underlying causes of the behavior (Foxx, 1982(Foxx, , 2003. Thus, it might be helpful for a client to have an alternative to SIB while working through some of the core, emotionally difficult, concerns.…”
mentioning
confidence: 99%